Advances in Dementia Research 2019
DOI: 10.5772/intechopen.83784
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Intervention to Promote Social Connectedness through Social Recreational Programs for Persons with Dementia: A Critical Analysis

Abstract: People living with dementia and their caregivers continue to experience social isolation and are impacted by consequential negative health impacts. Social recreational programs are community-oriented programs that aim to reduce the levels of social isolation among persons with dementia and their informal caregivers by providing the opportunity to strengthen their social network through an increased social participation in the community. The purpose of this chapter is to focus on the reduction of social isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our current study sample was predominately comprised of participants with Caucasian ethnic background, and individuals who are currently accessing dementia care programs. However, literature revealed that a reduced level of participation is observed in the dementia care and support programs among immigrants and refugees compared to their nonimmigrant counterparts (Sun, Clarke, et al, 2019). Therefore, there is an urgent need for ongoing evaluation to explore whether the existing social recreational programs are culturally appropriate in supporting the needs of people with dementia and their caregivers, as well as raising awareness about these programs and services to promote increased access and utilization by the program participants from diverse cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study sample was predominately comprised of participants with Caucasian ethnic background, and individuals who are currently accessing dementia care programs. However, literature revealed that a reduced level of participation is observed in the dementia care and support programs among immigrants and refugees compared to their nonimmigrant counterparts (Sun, Clarke, et al, 2019). Therefore, there is an urgent need for ongoing evaluation to explore whether the existing social recreational programs are culturally appropriate in supporting the needs of people with dementia and their caregivers, as well as raising awareness about these programs and services to promote increased access and utilization by the program participants from diverse cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…11 Broader community benefits can also result, for example, support for the continued participation of people with dementia in community activities can lead to generally enhanced understanding of dementia, which can have a significant effect on wellbeing of people living with dementia and their families. 12 Various types of community engagement activities are designed to ensure people living with dementia, their families and caregivers, are supported to retain their connection to the community. Such activities include co-creation programs, 13 reminiscence programs, 14 leisure activities, 15 physical and exercise activities, 16 and community gardening activities, 17 to name a few.…”
Section: Introductionmentioning
confidence: 99%